STATE RESPONSIBILITY IN LEGAL PROTECTION OF LABOR THROUGH CORPORATE APPROACH - Charda, Ujang (Universitas Islam Lamongan, 2023)
The purpose of this research is to find out the basic concept of labor protection in theIndonesian legal state and to analyze the application of the legal protection model forworkers through a corporatist approach. The research method used is analyticaldescriptive with a normative juridical approach through the library and field researchstages with data collection techniques through literature study. Then the data wereanalyzed through qualitative normative methods without using numbers andmathematical formulas. Based on the results of the study, it is shown that the type ofIndonesian labor law in legal protection of workers is a corporate model of labor lawthrough legislation in the form of legislation as an instrument of government policy.